ASSOCIATION OF ENDOGENOUS MINERALIZATION WITH EARTHQUAKE-PRONE INTERSECTIONS OF LINEAMENTS - Gvishiani A.D.; Gorshkov A.I. (My University, 1989)
The correlation of mineral deposits with fault nodes has long been known; the new aspect of the present treatment is the fact that most of the deposits considered are associated with potential high-seismicity nodes and that many of them are the sites of the strongest earthquakes recorded in the regions. This indicates that metallogeny and earthquake generation are likely to have common tectonic causes. The paper attempts to identify a mechanism that could cause earthquakes and endogeneous metal deposits to be associated with the same nodes.